2007
DOI: 10.1038/sj.eye.6702711
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of second eye clear corneal cataract surgery using assisted topical anaesthesia

Abstract: Aim To assess patient recall of intraoperative pain, anxiety, fear, and sensory (visual and auditory) perceptions during second eye clear corneal cataract surgery using assisted topical anaesthesia (ATA), in comparison with first eye cataract surgery using the same technique. Methods This prospective, consecutive, observational study was conducted in a free-standing dedicated ophthalmic day surgery centre. A voluntary questionnaire was distributed to 129 consecutive patients who underwent clear corneal catarac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 14 publications
3
41
2
1
Order By: Relevance
“…A common observation among ophthalmic surgeons is that patients often complain about more pain or ocular discomfort as they undergo ophthalmic procedures in their second eye when compared to the first. This issue has been reported both in cataract [4] and, although not being specifically addressed, in refractive surgery patients [5].…”
Section: Introductionmentioning
confidence: 97%
“…A common observation among ophthalmic surgeons is that patients often complain about more pain or ocular discomfort as they undergo ophthalmic procedures in their second eye when compared to the first. This issue has been reported both in cataract [4] and, although not being specifically addressed, in refractive surgery patients [5].…”
Section: Introductionmentioning
confidence: 97%
“…Similar observations have been published by other authors. 8,9 Although fear did appear to be associated with the first eye surgery in these studies, once again it failed to reach statistical significance.…”
Section: Reply To Dr Tanmentioning
confidence: 74%
“…Albeit, some examiners concluded that second eye surgeries would be more painful (6,20), others including us have could not find difference in the intaoperative pain between the consecutive surgeries for a patient (2,15,16,21). As the length (and complexity) of the procedure is of no influence on the pain sensitivity (55,57), the duration of the surgeries was not recorded.…”
Section: 8discussionmentioning
confidence: 88%
“…Data always were obtained from each patient's both eyes procedures (otherwise excluded) consequently, the compared groups did not differ in either age, gender, education level, psychological characteristics or racial distribution. Similar studies (6,16,21) in contrast, compared independent groups of patients undergoing the first and second eye PhEs, moreover the procedures were done by different surgeons. Taking into consideration, that a patient complaining about more pain or unpleasantness by the second eye surgery, actually he or she compares the recently perceived pain with the remembered pain of the first procedure, we decided to try to estimate the remembered pain of the procedures as well.…”
Section: 8discussionmentioning
confidence: 99%
See 1 more Smart Citation